Clinical profiling of psoriatic arthritis: an observational cross-sectional study from Karnataka Psoriatic Arthritis Cohort - Chanakya Kodishala; Vineeta Shobha; S Chandrashekara; Sharath Kumar; Vikram Haridas; Vijay K R Rao; Ramesh Jois; Manisha Daware; Yogesh Preet Singh; Shweta Singhai; B G Dharmanand; Pramod Chebbi; et al. (Indian Journal of Rheumatology)
Background: Clinical patterns and disease activity burden of psoriatic arthritis (PsA) varies in different parts of the world. There are limited studies from the Indian subcontinent. Aims: To study the cutaneous and articular profile of PsA and describe their disease activity with validated outcome measures. Methods: Karnataka psoriatic arthritis cohort study is a multicenter, prospective, cross-sectional, observational study which included all consecutive PsA patients defined by Classification criteria for psoriatic arthritis (CASPAR) from 18 rheumatology centers. Results: A total of 549 PsA patients (M: F: 6:5), mean age 38.4 (±14) years were included. PsA preceded psoriasis in 81 (14.7%) while simultaneous onset was noted in 117 (21.5%). Plaque lesions (330 [78.8%]) and scalp (210 [49.2%]) were the most common type and site. Mild, moderate, and severe skin disease was noted in 480 (80%), 50 (9.3%), and 57 (10.6%) patients, respectively. Mean disease activity in PsA (DAPSA) was 18.8 (16.6); 100 (19.9%) were in remission. Low, moderate, and high joint disease activity was found in 145 (28.8%), 137 (27.2%), and 123 (24.5%), respectively. There was no correlation between skin and joint disease. Polyarthritis (216 [40.7%]) and oligoarthritis (202 [38.1%]) were the most frequent PsA subtypes. Those with a higher DAPSA (>28) were older (P = 0.02), had a shorter duration of psoriasis (P = 0.02) and higher psoriatic area and severity index scores (P = 0.0001). Conclusions: We report high articular disease activity in half while cutaneous disease activity was minimal in majority.